Factors associated with peripheral intravenous catheter complications among hospitalised pediatric patients: a cross-sectional study - Ferika Indarwati; Sinta Dewi Refka Maula; Intan Sukmawati; Romdzati Romdzati; Dewi Caesaria Fitriani (Ners Muda, 2026)
Peripheral intravenous catheter (PIVC) complications are common in hospitalised children and may interrupt intravenous therapy. This study aimed to examine the associations of patient age, medical diagnosis, intravenous fluid type, and intravenous medication category with PIVC complications among hospitalised pediatric patients. This observational cross-sectional study was conducted at two teaching hospitals in Yogyakarta, Indonesia, from January to June 2025. A total of 120 pediatric patients meeting the study criteria were recruited using purposive sampling. Data were collected by trained observers using a validated observation checklist. Descriptive statistics, the Mann–Whitney U test, and Chi-square tests were used for analysis. PIVC complications were recorded in 57 of 120 patients (47.5%). Children with complications were younger than those without complications (mean age 53.9 vs 78.5 months; p = 0.002). Compared with respiratory diagnoses, gastrointestinal/ neurological/ immunological/ urinary diagnoses were associated with higher unadjusted odds of complications (OR = 9.91, 95% CI: 3.16–31.07), as were musculoskeletal/ integumentary diagnoses (OR = 10.13, 95% CI: 1.96–52.42). Intravenous fluid type (p = 0.056) and medication category (p = 0.277) were not significantly associated with PIVC complications. Younger age and medical diagnosis category were associated with PIVC complications in this sample. Because the estimates were derived from bivariate analyses, they should be interpreted cautiously. Prospective studies with catheter-level variables and multivariable adjustment are needed to clarify independent determinants of PIVC complications in pediatric patients.